2020
DOI: 10.1371/journal.pone.0227520
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the heterodimer model for mineralocorticoid and glucocorticoid receptor interactions in nuclei and at DNA

Abstract: Glucocorticoid (GR) and mineralocorticoid receptors (MR) are believed to classically bind DNA as homodimers or MR-GR heterodimers to influence gene regulation in response to pulsatile basal or stress-evoked glucocorticoid secretion. Pulsed corticosterone presentation reveals MR and GR co-occupy DNA only at the peaks of glucocorticoid oscillations, allowing interaction. GR DNA occupancy was pulsatile, while MR DNA occupancy was prolonged through the inter-pulse interval. In mouse mammary 3617 cells MR-GR intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 109 publications
(203 reference statements)
1
54
0
Order By: Relevance
“…Despite the high structural and functional homology between GR and MR, and in particular the identity in their DNA binding domain (greater than 90%), the global or epidermal-specific phenotypes of the knock-out mouse models for these transcription factors clearly indicate that they do not play overlapping functions 3 . It is thus expected that they regulate different gene subsets, as recently shown by in vitro and in vivo data 8 , 31 34 . It is also expected that the relative functions of GR and MR, either alone or combined depend on the cell-type.…”
Section: Discussionmentioning
confidence: 65%
“…Despite the high structural and functional homology between GR and MR, and in particular the identity in their DNA binding domain (greater than 90%), the global or epidermal-specific phenotypes of the knock-out mouse models for these transcription factors clearly indicate that they do not play overlapping functions 3 . It is thus expected that they regulate different gene subsets, as recently shown by in vitro and in vivo data 8 , 31 34 . It is also expected that the relative functions of GR and MR, either alone or combined depend on the cell-type.…”
Section: Discussionmentioning
confidence: 65%
“…Likewise, GR has been found to form a heterodimer with the mineralocorticoid receptor (MR) ( 34 ) in a number of different tissues and cells, including the hippocampus and mammary cells. Here, the GR-MR complex binds to GREs and regulates gene expression ( 131 , 132 ). Although a GR-MR complex has not, to our knowledge, been shown to be functional in the liver, it has been suggested that GR-MR could regulate hepatic expression of G6Pase ( 133 ) ( Figure 3B ).…”
Section: Gr Operates In Transcriptional Network To Control Hepatic Gmentioning
confidence: 99%
“…The GR and MR are closely related members of the nuclear receptor superfamily. In addition to a high degree of sequence conservation, GR and MR share overlapping hormone specificity, similarities of binding domain affinity and transcriptional activity at common hormone response elements (Pooley et al, 2020). However, GR and MR also display specific properties in terms of distribution, molecular action and ligand specificity (Mifsud and Reul, 2018;Pearce, 1994) as well as activation patterns in response to ultradian and stressinduced stimulation (Conway-Campbell et al, 2007;Mifsud and Reul, 2016).…”
Section: The Importance Of the Gr-mr Balancementioning
confidence: 99%
“…The interdependent actions of GR and MR also possibly result from their interaction in the nucleoplasm and at chromatin-associated DNA binding sites occurring during the peak of glucocorticoid oscillation and during the normal physiological stress response (Pooley et al, 2020). The precise mechanisms by which GR and MR interact at certain GREs are, however, still unclear.…”
Section: The Importance Of the Gr-mr Balancementioning
confidence: 99%
See 1 more Smart Citation